Determination of secondary school students' ability of making transitions between representations related to the - Kurnaz, Mehmet Altan; Bayri, Nezihe Gokcen; Ezberci, Ebru (SynthesisHub Advance Scientific Research, 2015)
The aim of this study was to reveal secondary school students' ability of making transitions between text, picture, table and graphic representations related to the electricity. The research is a case study of the qualitative research methods. The working groups of the study were totally 100 students, including 50 from each of 6th, 7th and 8th students, studying at a secondary school in the 2012-2013 academic year. To determine the students' status of transitions in representations, a measurement tool relating to the subject of electricity was developed by researches. The measurement consists open-ended questions which questioned transitions representations (text, images, tables and graphics) with each other. Document analysis method was used in data analysis. In this context, determining specific criteria, established codes in accordance with the given answers by the students and the questions was evaluated in certain dimensions. Consequently, students were found to be inadequate to present transitions in representations in electricity. When the results are evaluated, it was suggested that during the teaching of electricity topic, teaching practices to draw attention to transition between different representations and in measurement-assessment processes, the questions reflecting the transition between different representations should be given; regulation the assessment questions in textbooks in this direction is recommended.
Keywords: 4. Education